The Use of Information and Communication Technologies in Formation of an Inclusive Education System - V. Titkova, O.; V. Efremenko, V.; M. Osipova, A.; I. Zhemerikina, Yu. (International Journal of Engineering and Technology, 2018)
The present article discusses the role of information and communication technologies in inclusive education in accordance with government policies and the need to obtain equal access to quality education. Also, the possibilities and advantages of ICT and their aids in optimizing learning environment are described. Particular attention is focused on the role of new information technologies in this kind of training, and their advantages and disadvantages are listedÂ